WE HAVE THE RIGHT TO BREATHE CLEAN AIR REMARKS DELIVERED BY SUSAN BIANCHI - SAND, NATIONAL PRESIDENT ASSOCIATION OF FLIGHT ATTENDANTS, AFL-CIO SMOKING BAN NEWS CONFERENCE RAYBURN HOUSE OFFICE BUILDING WASHINGTON, D.C. JUNE 20, 1989 (Tufts Archival Research Center, 2007)
Report entitled “We have the right to breathe clean air,” delivered by Susan Bianchi-Sand, president of the Association of Flight Attendants AFL-CIO. Requests that the temporary ban on all domestic flights less than two hours be made permanent and extended to all flights. Discuses the benefits that have already been as a result of a partial ban. Highlights the success seen in a ban in Australia.